The effect of leverage on firms profitability: evidence from Malaysia / Farisha Audrina Sherwan - Sherwan, Farisha Audrina (2019)
This study is focusing on the relationship between the firms’ profitability and leverage of the top 50 firms that are listed in Bursa Malaysia that are selected based on the best revenue rank. The degree of operating, financial and total leverage have been compared with the firms’ profitability that indicate by the return on investment. By calculating some significant ratios, it helps us to conclude that there is a significant relationship between the degree of financial leverage and degree of total leverage with firms’ profitability (P = 0.052 and 0.013 respectively). However, this study will help financial manager with the better understanding about the use of leverage.